(untitled) (CIPEEX, 2022)
PARTIAL AGENESIS OF THE CORPUS CALLOSUM (PACC) IS A CONGENITAL MALFORMATION THAT GENERATES A DYSFUNCTION IN THE CONNECTION BETWEEN THE CEREBRAL HEMISPHERES, WHICH CAN IMPAIR LATERALIZED HEMISPHERIC FUNCTIONS, SUCH AS EMOTIONS, LANGUAGE, AND VISUAL SPATIAL PROCESSING. DUE TO COMPENSATION MECHANISMS AND BRAIN PLASTICITY, THERE ARE PATIENTS WITH HETEROGENEOUS CLINICAL MANIFESTATIONS, FROM ASYMPTOMATIC PATIENTS TO THOSE WITH MORE SEVERE CASES. THE OBJECTIVE OF THIS CASE REPORT IS TO DESCRIBE THE CASE OF A 14-YEAR-OLD PATIENT WITH ACC, THAT HAS AN EASE FOR LEARNING LANGUAGES.